Influence of nanosilica surface on thione-thiol tautomerism of grafted thiourea groups - Smirnova, O.V.; Grebenyuk, A.G.; Zub, Yu.L. (Поверхность, 2015)
The thione-thiol tautomerism has been investigated of thiourea groups grafted to silica surface in the presence of water molecules. The configuration of the transition state has been calculated by quantum chemical modeling of a N, N'-dimethylthiourea (DMTU) molecule in the forms of (CH₃)₂(NH₂)₂CS/CH₃NHCSHNCH₃ and of fragment silica clusters (HO)₃SiCH₂NHC(S)NHCH₃ with one water molecule (density functional theory method, B3LYP/6-31G (d, p)). The value of the total energy of the transition state with one water molecule and the activation energy of the thione-thiol tautomeric transition for different conformations of the system were obtained. The results of these calculations have shown that the activation barrier in the presence of a silica matrix decreases. The activation barrier in the studied systems is higher than that in similar systems in vacuum.